From economy to society? perspectives on transnational risk regulation - Lange, Bettina; Thomas, Dania, 1967-; Sarat, Austin (Studies in law, politics, and society ;, 2013)
This special issue asks what role society can play in the regulation of transnational risks, as an alternative to or at least significant addition to reliance on state regulatory activity and the myth of the self-regulatory capacity of markets (Stiglitz, 2001, p. xiii). How can a social sphere contribute to the prevention and management of risks, often transnational in nature, posed by economic activity?Leading socio-legal scholars explore whether and how the idea of harnessing the regulatory capacity of a social sphere provides a new analytical lens that can provide fresh insights into transnational risk regulation, and whether this idea helps to identify innovative approaches to regulating transnational risks.